IMPROVING THE STUDENTS’ SPEAKING ABILITY BY USING SMALL GROUP DISCUSSION (CLASSROOM ACTION RESEARCH AT SMPN 1 SEMEN) - Puspitasari, Dewi (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This study aims to inquire the use of small group discussion to improve the students’ speaking ability at eighth grade students of SMPN 1 Semen. The students’ average score in preliminary study was 57, 78 showed the students’ speaking ability was low. The research was implemented the Classroom Action Research (CAR). In this case, the eighth grade students of SMPN 1 Semen were taken as the sample consisting of 36 students. To find the result of this study, the researcher implemented the action in two cycles. The procedure of classroom action research was reconnaissance, planning, implementation of the action, observation, analysis and reflection in each cycle. To find the data, the researcher implemented the documentation, observation, interview, and testing. In the cycle 1, the researcher divided 6 small groups discussion consisting of 6 members. In the cycle 2 the researcher divided 9 small groups by reducing the members of group became 4 members and also facilited variety students’ speaking ability in each group to give much more opportunity of each student being more active in speaking. The result showed improvement. The average score in the cycle 1 was 69, 17 became reach upper the KKM (75) that was 78, 06 in the cycle 2. Based on the finding and discussion of this study, the strategy of teaching speaking by using small group discussion could improve the students’ speaking ability at the seventh grade students of SMPN 1 Semen in academic year 2014/2015.